Efektivitas Pendekatan Religius Berbasis Multimedia dalam Meningkatkan Kemampuan Penguasaan Konsep - Safitri, Erna Retna (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to determine the effectiveness of a multimedia-based religious approach in increasing students' mastery of concepts in the subject of ecosystems. The research was conducted using a quantitative approach using a quasi-experimental research design on first-level students (semester 1) who teach General Biology courses. The research was conducted using Randomized Control-Group Pretest-Posttest. Learning is presented by integrating religious values ​​that enable the learning process to be more meaningful. To obtain a better conclusion, a hypothesis test is carried out by analyzing the data from the research test results. The results showed that a multimedia-based religious approach was able to improve students' mastery of concepts as indicated by the normalized Gain value of 0.51 which was in the moderate category. Improvement especially in the aspects of remembering, understanding, applying, analyzing and creating. This learning model can be used so that science learning, especially biology, does not only touch cognitive aspects but also affective aspects which in turn will contribute to the formation of positive attitudes of students. Keyword : religious, multimedia, concept mastery, affektif